Digital transformation of regional enterprises: research, assessment, opportunities - Korokoshko Julia (π-Economy)
In the context of highly dynamic changes caused by the transition to Industry 4.0 and the digital economy, Russian enterprises must have up-to-date information about their development potential and real opportunities in order to adapt to the current conditions in a timely manner. This problem is especially relevant for representatives of the regional business community, many of whom have not yet realized the scale and depth of the necessary transformations. They remain unprepared for the onset of the industrial revolution and digitalization of the economy, which, of course, serves as a prerequisite for potential threats and risks of uncompetitiveness and even loss of business. The adopted course of our country on the formation of technological sovereignty, import substitution and digitalization of all domestic sectors of the Russian economy actualizes the topic of the study. In this regard, it is important to timely and objectively assess the opportunities and threats of digital transformation of Russian enterprises and take appropriate adequate measures to ensure their stable and sustainable development. The purpose of the study is to assess the awareness, perception and readiness of regional enterprises for digital transformation, conducted on the basis of marketing research methods, comparative and expert analysis. The study allowed us to obtain the following results: to study theoretical provisions that reveal the essence and content of digitalization and digital transformation; to assess the perception and readiness of regional enterprises for digital transformation; to identify practical results of the implementation of digital capabilities of regional enterprises; to identify the most promising areas of application of the possibilities of digitalization of business processes in the work of domestic enterprises. The results of the study demonstrate the current situation typical for the subjects of the Russian Federation (on the example of the Republic of Mordovia) from the perspective of digitalization of regional business and can serve as an indicator of assessing the readiness of its real state for the necessary digitalization of business processes. The results obtained indicate the mandatory need to systematically study the dynamically changing level of readiness of regional enterprises to adapt to digitalization, as well as to identify the factors hindering the digital transformation of modern companies.